Desejo, preconceito e morte: assassinatos de LGBT em Segipe 1980 a 2010 - Oliveira, Jose Marcelo Domingos de (2012)
This study examines the phenomenon of the murders of LGBT in Sergipe, between 1980 and 2010. Data were collected from newspapers, police, and judicial proceedings in the Courts with family members and friends of victims. The data show that despite the existence of death for involvement with drugs (crack), crimes of passion, among others, homophobia is one of its most characteristic elements. The victim profile also differs greatly from the aggressor, while the first is made up of individuals aged 25 to 44 years, the offender is between 15 and 29 years. Added to this the sensationalism of the press, the limits of police and justice in dealing with such events. The results seem to be forgetting some of the cases that do not reach the jury. It is an extensive study that combines statistical and qualitative data with a view to offering a closer look at the issue. The result is a mapping of brutal crimes, which, in part, has homophobia as the primary cause for its implementation